REVITALISASI USAHA KESEHATAN GIGI SEKOLAH (UKGS) DALAM MENINGKATKAN KESEHATAN GIGI DAN MULUT ANAK USIA SEKOLAH - I Gusti Ayu Pradnyani (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
School Dental Care in one of the community health centre (Puskesmas) programs which is intended for families and communities in its vacanity, Such program can be done in house or outdoors of the "Puskesmas" such as in schools, Posyandu (ntegrated Service Post), mobile clinic. School Dental Care is actually one part of community health care which is intended to maintain, improve the school student's dental and oral health. The form of activities which are made in School Dental Care include promotive activities, preventive activities, and curative activities.